Papua New Guinea Economic Update, January 2020 : Facing Economic Headwinds - World Bank (World Bank, Washington, DC, 2020)
Papua New Guinea’s economy continues to face economic headwinds resulting from global and domestic economic uncertainties. PNG’s real GDP, despite rebounding to 5.6 percent in 2019, is expected to fall and hover at around 3 percent on average between 2020¬ and 2022, posing many negative risks, including exposure to unexpected external shocks or potential domestic political and economic turbulence. Projected GDP growth rates are lower than our previous forecasts, mainly due to delays in finalizing agreements and launching implementation of large new resource projects. The other major factor that impacted the downgrade in the growth outlook include heightened global uncertainty due to (i) a partial nature of the recent trade deal between the United States and China and (ii) a fresh emergence of new risks to Chinese and global growth, including a novel coronavirus. The report also provides an in-depth examination of the relationship between inclusiveness of growth and human capital (the health, knowledge, skills and resilience people accumulate). The report evaluates the implications of recent trends and policy reforms alongside the government’s stated development objectives, emphasizing that increased investment in human capital will be a critical prerequisite to achieving quality and inclusive growth in PNG.